Traditional Knowledge on Some Ethnotoxic Plants Reported from Poonch District of J&K, India - Manzoor, Javed (Indian Forester, 2018)
Toxic plants represent a major class of noxious stuff known the world over. Besides influencing people directly, these also pose a serious threat to livestock rearing sector in term of monetary loss. The present study was conducted in Poonch District of J&K, India to gather and purposely document the traditional and customary information on poisonous plants and their effects prevailing among the people. 69 plant species belonging to 38 families and 62 genera were recorded from the study areas which possess certain poisonous characteristics. Maximum plant species were represented by family Fabaceae (08) followed by Solanaceae (06), Euphorbiaceae (06) and Asteraceae with 04 species.